Breast cancer screening programmes in selected European countries and Poland - Adam Jasiura; Izabela Dera; Karolina Szlachcic; Mateusz Gorzel; Joanna Zmonarska (Kazimierz Wielki University, 2021)
Breast neoplasms are the most common malignant tumors among women. In recent years breast cancer incidence rate has increased. Due to this fact the European Union presents evidence-based guidelines on breast cancer screening and diagnosis. Recommended and commonly used screening test is mammography. The effectiveness of prophylaxis is measured by a decrease in breast cancer mortality rate. Detailed recommendations in EU member countries differ from those presented by the EU institutions. This paper compares the screening programme in Poland to screening programmes in other EU members. The evaluation considers compliance with European screening guidelines and changes in mortality rates since the introduction of the screening programs. General guidelines in Poland are close to European ones. However, some Polish health centers still use analog mammography instead of recommended digital mammography. Furthermore, mortality rate changes in Poland maintain on a constant level due to women's reluctant participation in screening tests.